Physicochemical characteristics and fourier transform infrared spectroscopy (FTIR) analysis of non-cariogenic gummy candy as response to Chlorella vulgaris microalgae and xylitol sweetener - Khairi, Amalya Nurul; Oktafiany, Lintang Puja; Jebreen, Ali Mohammad Yousef (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
Gummy candies are popular semi-solid products but mostly are high in sucrose and low in nutritional value. Fortification with Chlorella vulgaris, which is rich in protein and micronutrients, and the use of xylitol as a low-calorie sweetener, has the potential to improve the functional quality of the product. This study aimed to evaluate the effect of variations in Chlorella vulgaris and xylitol on the physicochemical characteristics of gummy candies using a one-factor completely randomized design with five formulations (F0–F4). The analysis included physical properties (i.e., hardness, cohesiveness, gumminess, chewiness, adhesiveness), chemical properties (i.e., pH, total protein, soluble, insoluble), and functional groups through FTIR. The results showed that the treatment had a significant effect (p < 0.05) on all parameters. The best selected formulation produced a hardness of 2.37 N, cohesiveness of 0.78, gumminess of 0.84 N, chewiness of 1.21 Nmm, and total protein of 11.99%. The FTIR spectrum identified O–H bands at 3283.75 cm⁻¹, C–H at 2920.39 cm⁻¹, and Amide I at 1632.18 cm⁻¹, indicating interactions between components in the gel matrix. Overall, the combination of Chlorella vulgaris and xylitol produces high-protein gummy candies with good physicochemical quality and potential as functional foods supporting stunting prevention.